The Meaning of Housework (Domestic Sector) For the Left-Behind Husbands of Indonesian Female Migrant Workers in Dungmanten Village, Tulungagung Regency - Susilo, Singgih; Astina, I Komang (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
The narrowing opportunities of employment in the home country are the reason why many Indonesian people of working age become migrant workers overseas. The left-behind husbands of female migrant workers must play a double role as a head and a homemaker in the family. This research aimed to identify the underlying social context and the resultant meaning of housework according to the husbands. The analysis design was based on the phenomenological perspective introduced by Alfred Schutz. The results showed that the female population in the observed village decided to follow the flux of Indonesian workers migrating abroad, mostly to Hong Kong and Taiwan. Relying on the pay cut scheme for their departure to the destination countries, they were able to earn up to IDR 7 million per month (nearly USD 500). The left-behind husbands, ranging from 31 to 57-year-old male, accepted the responsibility of doing housework or working in the domestic sector because of economic constraint (‘because motive’) and the high income earned by their wives (‘in-order-to motive’). They interpreted housework as either (1) invisible underemployment or (2) main job.